Delayed Bone Age Might Accelerate the Response to Human Growth Hormone Treatment in Small for Gestational Age Children with Short Stature - Jung-Eun Moon; Cheol Woo Ko (International Journal of Endocrinology)
Purpose. Growth hormone (GH) treatment is recommended to improve growth and psychosocial problems in short stature children born small for gestational age (SGA). Although GH therapy in these patients has been extensively studied, the impact of therapy according to delays in bone age (BA) is not known well. Objective. To investigate the effects of GH therapy in SGA patients with short stature according to BA delay. Methods. We retrospectively analyzed changes in height SD score (SDS) and BA/chronological age (CA) after 6 and 12 months of GH therapy in patients grouped according to BA delay. We studied 27 SGA children with short stature in the pediatric endocrinology clinic of Kyungpook National University Children’s Hospital. Results. Of the 27 patients, 9 had <2 years of BA delay, while 18 had >2 years of delay. There were no significant differences between the two groups in terms of gestational age and weight at birth, height SDS, IGF-1 SDS, and growth hormone dosage at the beginning of therapy. However, height SDS increased significantly in the group with >2 years of BA delay after 6 months of GH therapy (−2.50 ± 0.61 vs −1.87 ± 0.82; p=0.037) and 12 months (−2.27 ± 0.70 vs −1.63 ± 0.65; p=0.002). When height SDS was compared between with and without GHD, there were no significant differences. Conclusions. Delayed BA (>2 years) may impact the response to GH treatment in SGA children with short stature.